2009
DOI: 10.22401/jnus.12.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxytocin on Sperm Function and Seminal Biochemistry of Asthenospermic Patients

Abstract: Semen samples of 90 asthenospermic patients were examined, then they were divided into three main equal groups. In the first group, Oxytocin (OT) addition in three concentrations (2, 4, and 6 IU/ml) with sperm preparation medium (SPM) to the semen samples was investigated. Changes in sperm function tests and seminal biochemistry was used as indicator of effect. Results indicated that a significant increase in sperm grade activity in 2 IU/ml OT with a tendency for a decrease in this motility parameter in higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Male problems may contribute to the commonest single defined cause of infertility. Analysis of etiology has been based on conventional semen profile with information analyzed on the volume of ejaculation, the concentration of spermatozoa, their motility, morphological appearance, and inter-ejaculate variability (1) . World Health Organization (WHO) (2) reported that, infertility becomes a public health problem when its frequency exceeds 15%.…”
Section: Introductionmentioning
confidence: 99%
“…Male problems may contribute to the commonest single defined cause of infertility. Analysis of etiology has been based on conventional semen profile with information analyzed on the volume of ejaculation, the concentration of spermatozoa, their motility, morphological appearance, and inter-ejaculate variability (1) . World Health Organization (WHO) (2) reported that, infertility becomes a public health problem when its frequency exceeds 15%.…”
Section: Introductionmentioning
confidence: 99%